Development Of Oscillating Water Column (OWC) - Mohd Tahir, Suhana (Universiti Sains Malaysia, 2006)
The main objective of this project is to develop and to design a model Oscillating Water Column or OWC. Oscillating Water Column or OWC is a device that being design to convert the wave energy into electrical energy to be used in daily life. Before it being converted to electrical energy, the energy that produced by this device is mechanical energy. New software has been used to design this device called FLUENT. This software is used to determine the air pressure that can be produced at the end of the duct of this device due to the wave motion that being captured in the chamber. A chamber with 5m × 5m × 5m size should be design to capture the pressure and at the end to determine the power it can produced. The result will be in graphical and it shown the graphic contour of the pressure level. A turbine can be design at the end of the duct to increase the velocity of the air through the duct. High speed of air is needed to produce the high power before it can be stored in the generator. A generator is being mounted at the end of the turbine to store the energy produced. At the end of this process an inverter is being put to convert the direct current to an alternating current before it can be distributed to the consumer.